Field notes and letter to Thomas H. Kent contributed by James J. Dinsmore, June 3, 1996 - Dinsmore, James J.et al (1996)
Spring report of birds and locations contributed by James J. Dinsmore. Also included is a letter from Dinsmore to Thomas H. Kent regarding additional bird sightings. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1996. Epson - sheet feed